Tinjauan Daya Dukung Abutment pada Jembatan Gantung Pantai Ina Marina Maluku Tengah: Reveiw of the Abutment Bearing Capacity on the Ina Marina Suspension Bridge, Central Maluku - Pormes, Selvi Christin; Frans, Pieter Lourens; Tahya, Hendrie (Litera Academica Publishing, 2025)
The suspension bridge located at Ina Marina Beach, Central Maluku, serves as a connector between two artificial islands with a total length of 52 meters. This bridge lacks a reinforcement design in the working drawings, and the superstructure has experienced settlement due to weaknesses in the foundation structure. This study aims to calculate the bearing capacity of the abutment under the applied loads and to design an appropriate reinforcement system. The calculation method used includes the Bridge Management System (BMS) and ultimate strength analysis, while the reinforcement design refers to the Indonesian National Standard (SNI) 03-2847-2002. The analysis results show that the bearing capacity of the abutment is influenced by a dead load of 5 tons, a live load of 3.92 tons, and a frictional load of 693.41 tons, with horizontal forces of 58.21 tons (Pa1) and 127 tons (Pa2). The ultimate bearing capacity (Qult) is 127.3 tons/m², while the allowable bearing capacity (Qall) is 42.43 tons/m². Based on these calculations, reinforcement planning was carried out for structural elements such as the bearing slab, tread slab, and cantilever, with adjusted reinforcement specifications to ensure the stability and safety of the bridge structure.